Radiographic Evaluation of Femoral Fractures Due to Road Traffic Accidents in Benin City - Blackie O.H; Ogbe O.C; Odiase D.E; Enoghase R.J; Blackie F.F; Olukayode S.B; Iyhobhebhe V.D (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Femoral fractures resulting from road traffic accidents (RTAs) are a major cause of morbidity in developing countries, particularly among economically active young adults. Despite the increasing rate of RTAs in Nigeria, there is a lack of localized data concerning the radiographic distribution and epidemiological characteristics of femoral fractures. This study provides region-specific baseline data for clinical decision-making and public health interventions. A retrospective descriptive study was conducted using patient case notes and radiographic records of 141 individuals with femoral fractures resulting from RTAs, presented at Erichris Diagnostic Centre, Benin City, between January 2019 and December 2022. Radiographs were evaluated to determine fracture location (proximal, middle, or distal third). Data were analyzed using SPSS version 20, and results were presented using descriptive and inferential statistics. Associations between fracture type, age, and gender were examined using Chi-square tests with significance set at p < 0.05. The majority of patients were males (87.2%) and within the 16–30-year age group (72.3%), with a mean age of 31.6 years. The right femur was affected in 55.3% of cases. Middle third femoral shaft fractures were the most prevalent (63.8%), followed by proximal (26.3%) and distal fractures (9.9%). There was no statistically significant association between gender and fracture type (p > 0.05) or between age group and fracture type (p > 0.05). This study demonstrates a high incidence of middle shaft femoral fractures among young adult males due to RTAs in Benin City. These findings highlight the urgent need for targeted road safety policies, improved trauma care infrastructure, and preventive strategies directed at high-risk groups. The data provided serve as a critical reference for orthopedic management and public health planning.